Virtual Community Cohesion: a Proposed Measurement Instrument - Yusop, Noriadah; Mat Aji, Zahurin; Md Dahalin, Zulkhairi (International Journal of Engineering and Technology, 2018)
Virtual community has become one of the interaction platforms that allows interactions among members of the community and thus could become a mechanism for a more established and broader relationship. The existence and prosperity of both physical and virtual community depends very much on cohesiveness among its members. Community cohesion is a popular concept that is used to describe the strength of human relationships and the stability of a more differentiated society. Prior study has been conducted to identify more inclusive indicators for the nine dimensions of a cohesion measurement framework as to come up with a reliable instrument for physical social cohesion. Based on the developed instrument for physical social cohesion, out of the nine dimensions, seven that are pertinent to virtual community are retained or revised: Trust in multi-ethnicities, Willingness to cooperate, Shared common values, Involvement in decision-making, Voluntarism, Safe-guard members, and Roles of administrator. Another study was then conducted to determine the indicators for the seven dimensions as an instrument for virtual community cohesion. Hence, this paper aims to elaborate on the development of the proposed instrument for measuring virtual community cohesion. The construction of the instrument is based on the seven steps of scale development and analysis namely Item Generation, Content Adequacy Assessment, Questionnaire Administration, Factor Analysis, Internal Consistency Assessment, Construct Validity, and Replication. However, only results up to the fifth step were included in this paper and the results suggest that the components that are significant to measure the virtual community cohesion are Perceived Membersâ€™ Influence, Membersâ€™ Characteristics and Community Participation. To confirm this, it is suggested that the subsequent steps be performed.Â